TANGGUNG JAWAB NEGARA DALAM PELAKSANAAN PEMENUHAN HAK NARAPIDANA OLEH LEMBAGA PEMASYARAKATAN BERDASARKAN HAK ASASI MANUSIA DI KOTA PEKANBARU (STUDI KASUS LEMBAGA PEMASYARAKATAN KELAS IIA PEKANBARU) - M Gilang Pratama; Firdaus Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Articles 9 and 10 paragraph 1 of Law Number 22 of 2022 concerning Correctionsare also referred to as the rights of convicts, including the right to education and teaching, theright to receive treatment, both spiritual and physical care, the right to receive proper healthand food services. Health is a condition that is not only free from disease but also covers allaspects of human life which include physical, emotional, social and spiritual aspects. One ofthe forms of not yet optimal guidance for prisoners in Class II A prison in Pekanbaru is in thehealth sector, almost 52% of prisoners still experience difficulties in fulfilling their right toproper health and food services. The formulation of the problems in this study are: first, Stateresponsibility in implementing the fulfillment of the rights of convicts by CorrectionalInstitutions based on Human Rights in Pekanbaru City (Case study of Pekanbaru Class IIAPenitentiary).This type of research is sociological legal research, because it is based on fieldresearch, namely by collecting data from interviews, questionnaires, and literature studiesthat are related to the problems to be studied, assisted by primary, secondary and tertiarydata. This research was conducted at the Kemenkumham Regional Office of Riau Provinceand Pekanbaru Class IIA Correctional Institution, while the population and sample are allparties related to the problem being studied. This research uses qualitative data analysis andproduces descriptive data.From the results of the study it can be concluded that, State responsibility in thiscase carried out by the Pekanbaru Class II A Correctional Institution for prisoners has beencarried out but has not been optimal. Lapas has provided the needs and rights of convictswhile in prison. Fulfillment of Prisoners' Rights by Correctional Institutions Based on HumanRights in the City of Pekanbaru (Case Study of Class II A Correctional Institutions ofPekanbaru) which are experiencing over capacity are still not running optimally. There arestill prisoners who feel that their rights have not been fulfilled. These rights include thefulfillment of the right to proper health care, a proper place to rest, the right to worshipproperly, the right to complain, and time for family visits.Keywords: Fulfillment-Human Rights-Justice.